Peran Majelis Perpustakaan dan Informasi Pimpinan Wilayah Muhammadiyah Sumatera Selatan dalam Pencegahan Hoax Covid-19 - Etty Nurmala Fadillah; Tutik Fitri Wijayanti (Fakultas Agama Islam Universitas Billfath, 2023)
The general purpose of this study is to determine the role of the Library and Information Council of the Muhammadiyah Regional Leaders of South Sumatra in preventing Covid-19 hoaxes among Muhammadiyah members. The scope of this research is the Library and Information Council of Muhammadiyah South Sumatra and Muhammadiyah people of South Sumatra. This research is important because the Muhammadiyah association can find out the extent of Muhammadiyah citizens' knowledge of Covid-19 and the lack of work programs made by the Muhammadiyah Library and Information Council of South Sumatra in an effort to achieve Muhammadiyah's vision and mission. The research method used is a quantitative and qualitative approach. Collecting data using a questionnaire instrument, in-depth interviews using open-ended questions, and documentation. The results showed that the Library and Information Council of the Muhammadiyah Regional Leaders of South Sumatra had a very important role in preventing hoax news about Covid-19 among Muhammadiyah members. These important roles include: actively sharing factual news and educating Muhammadiyah members who share hoax news through social media. Opening an online discussion service if there are Muhammadiyah members who want to ask about the truth of a news story.